Transparency and Thermal Stability of Silica Aerogel Synthesized From Sodium Silicate Using Ambient Pressure Drying - Hardiane, Egiana Reshi; Purba, Gita Evi Monika; Dahliyanti, Ayu (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
Silica aerogel is a special material due to its low density, high transparency, and high thermal stability. Producing silica aerogels in an inexpensive and environmentally friendly way is the focus of recent research. Here, silica aerogel is synthesized from sodium silicate as silica source and surface modification with organosilanes, followed by ambient pressure drying at various conditions. The resulting aerogels were analyzed for their density, transparency, and thermal stability. Silica aerogel with a low density of 0.4031 g/cm3 was successfully synthesized with polydimethylsiloxane (PDMS) as modifying agent at 7:50 solvent ratio. The aerogel can withstand heat up to 400°C.This shows the potential of aerogel to be applied as thermal insulator in various fields.